Computational intelligence in control - Ruano, Antonio (2014)
This Milestone Report addresses first the position of the areas of computers, computational intelligence and communications within IFAC. Subsequently, it addresses the role of computational intelligence in control. It focuses on four topics within the Computational Intelligence area: neural network control, fuzzy control, reinforcement learning and brain machine interfaces. Within these topics the challenges and the relevant theoretical contributions are highlighted, as well as expected future directions are pointed out.